Sustainability analysis of ornamental plants farming in Makassar - Tiasmalomo, Riska; Rukmana, Didi; Mahyuddin, Mahyuddin; Putra, Ridha Anugerah (Ornamental Horticulture, 2021)
This study aims to analyze the sustainability index of each dimension of ecology, economy, social, and technology as well as identify sensitive attributes that determine the sustainability of ornamental plant farming in Makassar. The rapid appraisal for program modified from rapid appraisal for fisheries program using the multidimensional scaling (MDS) method was used as the analytical instrument. MDS ordination analysis results showed the sustainability index value of each dimension, namely ecology (37.30), economic (40.90), social (31.74), and technology (34.33) were categorized as less sustainable with an average index value of all dimensions was 36.07. The leverage analysis visualizes that 9 out of 17 attributes has shown to be sensitive attributes that affect the business sustainability of ornamental plant in Makassar, namely frequency of crop waste management, water sources, utilization of plant waste, market scale, profitability, business land status, company registration certificate, use of modern technology, and frequency of environmentally friendly technology usage. Government should provide special business zones for ornamental plant so that all ornamental plant farmer in Makassar can be grouped into one zone. Furthermore, it can increase gross regional domestic product, employment opportunities, and opening up opportunities of other industrial sectors growth.